Determinación de la actividad agroproductiva y su relación con las potencialidades agroecológicas en la ciudad de Tamshiyacu, Loreto. 2019 - Vargas Piña, Jill Bencky (2022)
The theme was “Determination of agro-productive activity and its relationship with agroecological potential in the city of Tamshiyacu, Loreto. 2019. The objectives: to carry out a diagnosis of the agro-productive reality of the community and determine the agro-ecological potentialities to make a theoretical model of an Agro-ecological Plot with the purpose of improving the quality of life of its inhabitants in the Family Productive Units (UPF). Simple probabilistic sampling was used; through the application of descriptive statistics, the survey form was interpreted. The sample was 53 owners. The variables taken into account for the study are: soil typologies, use or extraction of water, meteorological data of the area, crops, cultural tasks that are developed in the sowing of plant species, breeding animals, fish, birds and use From handwork. It is concluded that the agro-productive activity has transfigured the social environment of the area, there is the heyday of cocoa cultivation, which brought some interruption of traditional productive activities in this area, due to the little interest in traditional crops (Umarí, pineapple, chestnut). . The production surfaces have low productivity, due to: crops without maintenance, little public investment in the agricultural sector and the forgetfulness of it, instability of market prices and partly decreasing demand for new agricultural products implemented in the city, in plots of small parceleros.